Increased TRPP2 expression in vascular smooth muscle cells from high‐salt intake hypertensive rats: The crucial role in vascular dysfunction. Issue 2 (20th November 2014) - Zhao, Ren; Zhou, Muyao; Li, Jie; Wang, Xia; Su, Kunli; Hu, Juncheng; Ye, Yong; Zhu, Jinhang; Zhang, Gongliang; Wang, Kai; Du, Juan; Wang, Liecheng; et al.
<x xml:space="preserve">Abstract</x> Scope High‐salt intake is a major risk factor in the development of hypertension. The underlying mechanism of high sodium on the cardiovascular system has received extensive attention. TRPP2 (Polycystin‐2) is a Ca2+ permeable nonselective cation channel that mediates Ca2+ mobilization to control vascular smooth muscle cells (VSMCs) contraction. Here, we investigated TRPP2 expression change in VSMCs from high‐salt intake hypertensive rats and role of TRPP2 in the development of high‐salt diet‐induced hypertension. Methods and results After 4 ws of dietary treatment, systolic blood pressure was significantly elevated in high‐salt intake rats (132 ± 3 mmHg) compared with regular diet control rats (104 ± 2 mmHg). Results from vessel tension and diameter measurements show that high‐salt intake potentiated phenylephrine‐induced contraction in denuded mesenteric artery and thoracic aorta. Immunoblot and immunofluorescence data indicate that TRPP2 expression in VSMCs from mesenteric artery and thoracic aorta was significantly increased in high‐salt intake‐induced hypertensive rats. However, agonist‐induced contractions in denuded mesenteric artery and thoracic aorta were markedly decreased if TRPP2 was knocked down by specific shRNA. Conclusion Our data demonstrate that high‐salt intake increased TRPP2 expression in VSMCs, which in turn potentiated blood vessel response to contractors; this may participate in the development of hypertension.